1983
DOI: 10.1080/03014468300006641
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the growth of ethnic Chinese children living in London

Abstract: Height, weight and triceps skinfold thickness of children aged 5 years and under were measured in a semi-longitudinal study of 50 Chinese families in London. Heights and weights of their mothers were also measured once. The children were taller and heavier than Chinese children in Hong Kong, but height-forage, when expressed as a percentage of the UK median value, declined after two years of age. The pattern of growth of triceps skinfold did not conform to the UK standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…The same was true of Japanese born in Hawaii (SHAPIRO, 1939) or Chinese born in London who were taller than those born in Hong Kong (WHEELER and TAN, 1983). These findings suggest that the improvement in living conditions and food intake, as well as exogamy, affect child growth and body dimensions in the …”
Section: Discussionsupporting
confidence: 51%
“…The same was true of Japanese born in Hawaii (SHAPIRO, 1939) or Chinese born in London who were taller than those born in Hong Kong (WHEELER and TAN, 1983). These findings suggest that the improvement in living conditions and food intake, as well as exogamy, affect child growth and body dimensions in the …”
Section: Discussionsupporting
confidence: 51%
“…Studies on the relationship between geographical migration and body height are well known (Kobyliansky & Arensburg, 1977;Kim, 1982;Wheeler & Tan, 1983;Bernis, 1984;Steegmann, 1985;Singh & Harrison, 1996) and many researchers have found that both internal and international migrants are taller than non-migrants (Bernis, 1984;Mascie-Taylor, 1984;Danubio et al, 2005;Szklarska et al, 2008), which was clearly confirmed in the present study. Migrants were taller, on average, than non-migrants by 1.4 cm in fathers and 2 cm in sons (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…The mid-arm circumference is greater in the Chinese Italian children, while the triceps and subscapular skinfolds are slightly thicker in the sample of He et al (2001). Our finding of a higher growth rate for Chinese children living in Italy than for those living in China agrees with the observation of Wheeler and Tan (1983) that Chinese children in London had higher length values than Chinese children in China, and with the observation of Wu and Daniel (2001) that Chinese-American infants were significantly heavier and longer than Chinese infants born and raised Taiwan. Other comparisons with Chinese children living in other industrialized countries yielded the following results.…”
Section: Comparisonssupporting
confidence: 93%